Review of the genus Diduga (Lepidoptera, Erebidae, Arctiinae) of Vietnam, with a new species and two newly recorded species - Bayarsaikhan, Ulziijargal; Heppner, John B.; Kwon, Hyung Wook; Bae, Yang-Seop (Zootaxa, 2024)
Species of the genus Diduga Moore are reviewed in Vietnam, with nine species including a new species, D. laocai sp. nov., and two newly recorded species, D. hastata Bayarsaikhan & Bae, 2021 and D. robdevosi Bayarsaikhan & Bae, 2023. Illustrations of adults and male and female genitalia of all examined species are provided.